1999
DOI: 10.1590/s0103-50531999000500008
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental investigation of the formation of E- and Z-Aldimines from the reaction of methylamine with acetaldehyde

Abstract: A reação entre metilamina e acetaldeído em pentano a 230 K leva à formação das aldiminas Ee Z-, sendo o isômero Z-o produto principal e gerado sob controle cinético. O isômero E-é mais estável do que o Z-por 3.3 kcal/mol (∆G*). Os cálculos ab initio mostraram que a etapa bimolecular de adição ocorre por um processo concertado, com formação da ligação C-N e transferência de próton através de um estado de transição de quatro centros. O intermediário zwiteriônico, frequentemente invocado neste tipo de reação, não… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
(38 reference statements)
2
12
0
Order By: Relevance
“…The E,E configuration is proposed as the most stable for benzilosazones according to published studies, 21 while for monoimines the relative stability of the E or Z configuration depends on the substituent groups. 22 As reported in the experimental part and discussed below, a Z,Z configuration was found for benzil bis(ethanolimine) (3a) and benzilosazone (4a).…”
Section: Reactions With Primary Aliphatic Aminessupporting
confidence: 56%
“…The E,E configuration is proposed as the most stable for benzilosazones according to published studies, 21 while for monoimines the relative stability of the E or Z configuration depends on the substituent groups. 22 As reported in the experimental part and discussed below, a Z,Z configuration was found for benzil bis(ethanolimine) (3a) and benzilosazone (4a).…”
Section: Reactions With Primary Aliphatic Aminessupporting
confidence: 56%
“…Previous theoretical studies have not considered the solvent effect in the geometry optimizations. 13,34 However, the electronic energies are in agreement. Our Eel barrier (M06-2X) is 22.9 kcal mol -1 while Pliego et al have reported a value of 26.7 kcal mol -1 using single point MP2 calculations on the gas phase Hartree-Fock geometries.…”
Section: Neutral Medium: Carbinolamine Formation Does Not Occur Through Direct Nucleophilic Attackmentioning
confidence: 79%
“…Our Eel barrier (M06-2X) is 22.9 kcal mol -1 while Pliego et al have reported a value of 26.7 kcal mol -1 using single point MP2 calculations on the gas phase Hartree-Fock geometries. 34 The solvent effect is very important to stabilize this TS, because the gas phase G ‡ is high, 34.4 kcal mol -1 . Nevertheless, we have found that in aqueous solution TS1 does not connect methylamine and acetaldehyde reactants to MS3 (carbinolamine).…”
Section: Neutral Medium: Carbinolamine Formation Does Not Occur Through Direct Nucleophilic Attackmentioning
confidence: 99%
“…The presence of an excess of formic acid suggests that both ionic species can be present in the reaction mixture. However, although it is known that the formation of open species is favoured in the ring-chain tautomeric equilibrium of aminals under acid conditions [29][30], the lifetime of aliphatic iminium ions in an aqueous solution is quite short [31].…”
Section: Resultsmentioning
confidence: 99%